Randomized evaluation of live attenuated vs. inactivated influenza vaccines in schools (RELATIVES) pilot study: A cluster randomized trial. Issue 4 (15th January 2015) - Kwong, Jeffrey C.; Pereira, Jennifer A.; Quach, Susan; Pellizzari, Rosana; Dusome, Edwina; Russell, Margaret L.; Hamid, Jemila S.; Feinberg, Yael; Winter, Anne-Luise; Gubbay, Jonathan B.; Sirtonski, Brittany; Moher, Deanna; et al.
Abstract Background School-based influenza immunization can effectively address accessibility barriers, but injected inactivated influenza vaccines (IIV) may not be acceptable to some children and parents in school settings. Objectives To better understand the feasibility of offering intranasal live attenuated influenza vaccines (LAIV) through schools, we assessed uptake, stakeholder acceptability, and cost of school-based delivery of LAIV compared to IIV. Methods We piloted an open-label cluster randomized trial involving 10 elementary schools in Peterborough, Ontario during the 2013–2014 influenza vaccination campaign. Schools were randomized to having students receive IIV or LAIV at publicly-funded school-based clinics organized by the local public health department. We measured the percentage of students vaccinated with at least one dose of influenza vaccine at school. Stakeholder acceptability was evaluated through a questionnaire of parents and interviews of public health department personnel and school principals. We compared the costs per dose of vaccine administered, including staff time and costs of vaccines and supplies. Results Single-dose influenza vaccine uptake was higher for the five schools offering LAIV than for the five offering IIV (19.3% vs. 12.2%, p = 0.02). Interviews with nine school principals and five public health department personnel suggested that the clinics ran smoothly with little disruption to school routines, and that LAIV was associated with increased efficiency and calmer children. All interviewees cited unfamiliarity with LAIV and the study recruitment package length as potential reasons for low uptake. The cost per vaccine dose administered was $38.67 for IIV and $43.50 for LAIV. Conclusions Use of LAIV in school-based clinics was associated with increased vaccine uptake and the perception among immunizing staff of reduced child anxiety, but also slightly higher vaccine administration costs, compared to IIV. However, uptake was low for both groups. More effective strategies to promote influenza vaccines and to obtain parent consent may improve vaccine uptake. Trial registration ClinicalTrials.gov NCT01995851. Funding Public Health Agency of Canada/Canadian Institutes of Health Research Influenza Research Network.